Removal effect of algicidal modified clay on Phaeocystis globosa blooms in culturing enclosure experiments: A short communication. Issue 1 (November 2021) - Qin, X; Chen, X; Li, F; Ya, H; Zhu, D; Dong, D; Su, X; Chen, B; Zhang, R
Abstract: With the increased scale of marine aquaculture in the Beibu Gulf, as well as accelerating urbanization and industrialization, frequent harmful algal blooms (HABs) have occurred in this area, especially those formed by Phaeocystis globosa in the past several years. As the P. globosa bloom has been a serious marine ecological disaster in the Beibu Gulf, research on quick and effective methods to eliminate P. globosa blooms is a hot research topic. In this study, the bacteria Streptomyces yatensis B4503 combined with modified diatomite was used to prepare algicidal modified clay, which was then used to study the removal effect on P. globosa blooms in field culture enclosures. The results showed that after 6 h of treatment with algicidal modified clay, compared with the blank control group, the cell density and chlorophyll a content of P. globosa decreased by 26.86% and 64.03%, respectively, and they decreased by 75.23% and 84.81%, respectively, after 24 h. The study indicated that algicidal modified clay can be applied to eliminate HABs caused by P. globosa in coastal water.